2005
DOI: 10.1111/j.1087-0024.2005.200414.x
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Being Big

Abstract: The ultimate stem cell, the oocyte, is frequently very large. For example, Drosophila and Xenopus oocytes are approximately 10(5) times larger than normal somatic cells. Importantly, once the large oocytes are fertilized, the resulting embryonic cells proliferate rapidly. Moreover, these divisions occur in the absence of cell growth and are not governed by normal cell cycle controls. Observations suggest that mitogens and cell growth signals modulate proliferation by upregulating G1-phase cyclins, which in tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…In support, large cells tend to divide faster than small cells [8]. One group found that both the expression and the activity of G1-phase cyclins are modulated by growth rate and cell size in yeast, suggesting that the proliferative capacity correlates with cell size and cell growth rates, such that the largest cells begin to proliferate five times faster than the smallest cells [9]. Other experiments in mammalian cells support the conclusion that cell size correlates closely with the proliferative potential of cells [1012].…”
Section: Stem Cells and Cell Sizementioning
confidence: 99%
“…In support, large cells tend to divide faster than small cells [8]. One group found that both the expression and the activity of G1-phase cyclins are modulated by growth rate and cell size in yeast, suggesting that the proliferative capacity correlates with cell size and cell growth rates, such that the largest cells begin to proliferate five times faster than the smallest cells [9]. Other experiments in mammalian cells support the conclusion that cell size correlates closely with the proliferative potential of cells [1012].…”
Section: Stem Cells and Cell Sizementioning
confidence: 99%
“…Variability in the duration of the G 1 phase has been well established [22] and G 1 -less cells occur during embryogenesis, in mutant mammalian cells [23]. Here, we propose that each cell division creates a proter-like and opisthe-like cell line, and further that the proter-like cell (arbitrarily) has an inherent bias in its expected inter-division time while the opisthe-like cell line does not.…”
Section: Probabilistic Model For G 1 Phase Durationmentioning
confidence: 73%
“…A blue whale is a cooperative group of about 100 quadrillion cells (Zhang et al 2005). In order for such a large and complex multicellular organism to have evolved, the single-celled ancestor of this species must have joined together to form a cooperative multicellular group (Maynard Smith and Szathmary 1995;Grosberg and Strathmann 2007;Michod 2007;Bourke 2011;Claessen et al 2014;West et al 2015).…”
mentioning
confidence: 99%